2018
DOI: 10.1017/s0007114517003762
|View full text |Cite
|
Sign up to set email alerts
|

Dairy product consumption is associated with pre-diabetes and newly diagnosed type 2 diabetes in the Lifelines Cohort Study

Abstract: Previous studies show associations between dairy product consumption and type 2 diabetes, but only a few studies conducted detailed analyses for a variety of dairy subgroups. Therefore, we examined cross-sectional associations of a broad variety of dairy subgroups with pre-diabetes and newly diagnosed type 2 diabetes (ND-T2DM) among Dutch adults. In total, 112 086 adults without diabetes completed a semi-quantitative FFQ and donated blood. Pre-diabetes was defined as fasting plasma glucose (FPG) between 5·6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 47 publications
3
41
0
8
Order By: Relevance
“…This study demonstrated an increased risk for T2DM by milk consumption in five of eight countries . The Dutch Lifeline Cohort Study with 112 086 participants investigated the association of nonfermented milk products, milk, and fermented milk products on participants with prediabetes (defined as fasting plasma glucose between 5.6 and 6.9 mmol/L or HbA1c of 5.7%‐6.4%) and newly diagnosed T2DM (defined as fasting plasma glucose ≥7.0 mmol/l or HbA1c ≥ 6.5%) . A positive association between full‐fat milk consumption (150 g/day) as well as nonfermented dairy products with prediabetes has been shown.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…This study demonstrated an increased risk for T2DM by milk consumption in five of eight countries . The Dutch Lifeline Cohort Study with 112 086 participants investigated the association of nonfermented milk products, milk, and fermented milk products on participants with prediabetes (defined as fasting plasma glucose between 5.6 and 6.9 mmol/L or HbA1c of 5.7%‐6.4%) and newly diagnosed T2DM (defined as fasting plasma glucose ≥7.0 mmol/l or HbA1c ≥ 6.5%) . A positive association between full‐fat milk consumption (150 g/day) as well as nonfermented dairy products with prediabetes has been shown.…”
Section: Introductionmentioning
confidence: 74%
“…A positive association between full‐fat milk consumption (150 g/day) as well as nonfermented dairy products with prediabetes has been shown. Notably, a significant positive association between milk (serving 150 g/day) and predominantly skimmed milk consumption (150 g/day) with T2DM has been detected …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Terdapat hubungan yang signifikan antara konsumsi total dairy dengan diabetes melitus tipe 2 di Belanda Bagian Utara dan Belanda Bagian Selatan (p<0,05). 18,19 Di Malaysia, diabetes melitus tipe 2 berhubungan dengan skor HbA1c (p<0,05). 20 Di Spanyol, konsumsi susu ≤14 kali dalam seminggu berhubungan dengan diabetes melitus (p<0,05).…”
Section: Hubungan Konsumsi Susu Dan Produk Olahannya Dengan Kejadian unclassified
“…Berdasarkan hasil penelitian di Belanda, konsumsi produk skim tidak berhubungan dengan kejadian diabetes melitus tipe 2, baik di Belanda Bagian Utara maupun Bagian Selatan (p>0,05). 18,19 Hasil ini berbanding terbalik dengan produk yogurt dimana konsumsi yogurt berhubungan secara signifikan dengan kejadian DMT2 di kedua bagian Negara Belanda tersebut (p<0,05; OR<1). 18,19 Kemudian pada penelitian di Belanda Bagian Utara, produk buttermilk (OR > 1) dan minuman yogurt (OR<1) berhubungan secara signifikan dengan DMT2 di Belanda Bagian Utara (p<0,05).…”
Section: Hubungan Konsumsi Susu Dan Produk Olahannya Dengan Kejadian unclassified